Soybean seed quality in relation to days between development stages - Vaughan, Duncan A.; Bernard, R.L.; Sinclair, J.B. (Wiley, 1989)
Seed quality in soybean, Glycine max (L.) Merr., considering infection by seed pathogens, overall visual quality, and seed weight, is affected by date of maturity. We report on the relationship between seed quality, genotype, and late reproductive growth periods and discuss these results in relation to breeding for improved seed quality. The objectives of this study were to: (i) measure seed quality in genetically similar germplasm, but which differ in date of maturity, and (ii) to determine the effects of different reproductive growth periods on seed quality. The field experiments were conducted on Brenton (fine‐silty, mixed, mesic Aquic Argiudolls), Flanagan (fine, montmorillonitic, mesic Aquic Argiudolls) or Proctor (fine‐silty, mixed, mesic Typic Argiudolls) soils at the Agronomy‐Plant Pathology Farm, Univ. of Illinois at Urbana‐Champaign. Delayed maturity in male‐sterile and depodded soybeans resulted in increased seed infection by field seed pathogens probably by lengthening the period during which infection and colonization could take place. Early maturing, maturity isolines were associated with increased infection by Phomopsis spp. which is related to favorable environmental conditions such as warm temperatures and high humidity, which favor spread and growth of this pathogen. A positive relationship was also found between the length of time for late seed fill (Reproductive growth stages R6 to R7) and seed infection by Phomopsis spp.